External Factor Prediction of Dengue Fever Spread in Surabaya using Geospatial Weighted Regression - Reyner Shenjaya Giri Putra; Siana Halim (Jurnal Titra, 2022)
Surabaya is the second largest city in Indonesia with high density population which can cause many living problem such as dengue fever. Dengue fever outbreak is caused by Aedes aegepty and spread fast in high density population. Many researches about dengue fever had been done in other city and country in order to decrease the spread of this outbreak. This research’s aim is to predict external factor that can caused dengue fever outbreak in Surabaya. Method that is used in this paper is Geospatial Weighted Regression (GWR) which focus on local coefficient estimates at each health centres in Surabaya. Health centres that have high local coefficient estimates have strong correlation of spreading dengue fever in Surabaya. This research’s only focused 3 external factor in which consist of family poverty percentage, precipitation, and levels of education. Levels of education is the only factor that have high local coefficient estimates and have strong correlation of spreading dengue fever in Surabaya compared to the other factors.